Preoperative Thrombocytopenia May Predict Poor Surgical Outcome after Extended Hepatectomy - Mohammad Golriz; Omid Ghamarnejad; Elias Khajeh; Mohammadsadegh Sabagh; Markus Mieth; Katrin Hoffmann; Alexis Ulrich; Thilo Hackert; Karl Heinz Weiss; Peter Schirmacher; Markus W. Büchler; Arianeb Mehrabi (Canadian Journal of Gastroenterology and Hepatology)
Background. It is a novel idea that platelet counts may be associated with postoperative outcome following liver surgery. This may help in planning an extended hepatectomy (EH), which is a surgical procedure with high morbidity and mortality. Aim. The aim of this study was to evaluate the predictive potential of platelet counts on the outcome of EH in patients without portal hypertension, splenomegaly, or cirrhosis. Methods. A series of 213 consecutive patients underwent EH (resection of ≥ five liver segments) between 2001 and 2016. The association of preoperative platelet counts with posthepatectomy liver failure (PHLF), morbidity (based on Clavien-Dindo classification), and 30-day mortality was evaluated using multivariate analysis. Results. PHLF was detected in 26.3% of patients, major complications in 26.8%, and 30-day mortality in 11.3% of patients. Multivariate analysis revealed that the preoperative platelet count is an independent predictor of PHLF (odds ratio [OR] 4.4, 95% confidence interval [CI] 1.3–15.0, p=0.020) and 30-day mortality (OR 4.4, 95% CI 1.1–18.8, p=0.043). Conclusions. Preoperative platelet count is associated with PHLF and mortality following extended liver resection. This association was independent of other related parameters. Prospective studies are needed to evaluate the predictive role and to determine the impact of preoperative correction of platelet count on postoperative outcomes after EH.